The observation and analysis of stellar photospheres - Gray, David F. 1938- (Cambridge University Press, 2005)
The Observation and Analysis of Stellar Photospheres describes the equipment, observational techniques, and analysis used in the investigation of stellar photospheres. This third edition builds on the success of the previous editions, improving the presentation, and revising topics and results to keep up to date with the latest research. The first half of the book develops the tools of analysis and the second half demonstrates how they can be applied. Topics covered include radiation transfer, models of stellar photospheres, spectroscopic equipment, observing stellar spectra, and techniques for measuring stellar characteristics. Useful real star data can be found throughout the text and in the appendices, and there are extensive references to the primary literature. This comprehensive textbook is suitable for advanced undergraduates and graduate students of stellar physics. Each chapter contains exercises to test understanding and a wealth of useful reference material is included
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Stellar photospheres; Stellar photospheres / Observations